PENGARUH INVESTMENT OPPORTUNITY SET TERHADAP STRUKTUR MODAL DAN DAMPAKNYA TERHADAP RETURN SAHAM (Studi Pada perusahaan food and Beverages yang terdaftar di Bursa Efek Indonesia) - Kartika Aji; Nur Khusniyah I (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Investment is the number of funds or other resources were done at this time, with the goal of obtaining a number of advantages in the future. Basically the purpose of investors to invest is to get a return. One alternative investments can be made in the stock market. Stock returns are influenced by the rate of growth and the company's capital structure policy. This study aims to determine the effect of investment opportunity set and capital structure to stock return, and the effect of investment opportunity set to capital structure. The population used in this study are all food and beverages company listed on the Indonesia Stock Exchange during the period 2009-2014. Sampling with purposive sampling method of determining the sample with the criteria that have been established and obtained a sample of 8 companies. The data analysis technique used is using partial least square method. The results showed that the investment opportunity set does not have a significant effect on stock returns, while the capital structure does not have a significant effect on stock returns and investment opportunity set does not have a significant effect on the capital structure. Keywords : stock return, investment opportunity set, capital structure